Does social support predict increased use of dental services in older men?. (21st April 2022) - Shu, C‐C; Wright, FAC; Naganathan, V; Blyth, FM; Le Couteur, DG; Handelsman, DJ; Stanaway, FF
Abstract: Background: Past research on social support and dental visits in older people has been limited by cross‐sectional design, limited social support dimensions and non‐representative samples. Methods: Data came from men with natural teeth completing Waves 3 and 4 of the Concord Health and Ageing in Men Project in Sydney, Australia. The relationship between social support at Wave 3 (2011–2012) and at least one dental visit per year at Wave 4 (2014–2016) was examined by Poisson regression. Social support was measured by structural (marital status, living arrangements, family support and social interaction) and functional (social support satisfaction) domains. Results: About 673 men were analysed. Structural and functional social support were not associated with the pattern of usual dental visits 5 years later in univariable or multivariable analyses. The only consistent significant factor was income source, with older men who had other sources of income more likely to regularly visit the dentist than older men solely reliant on the pension for income (prevalence ratio: 1.31, 95% CI: 1.13–1.52). Conclusions: We found no differences in the pattern of usual dental visits between older men with different levels and types of social support. For older Australian men, income source seems to be the most important determinant of regular dental visits. © 2022 Australian Dental Association